STUDY ON STRENGTH BROKE AND ELONGATION YARN POLYAMIDE ( PA ) WITH THE ADDITION OF SKIN STEM EXTRACT SALAM ( Syzygium polyanthum ) , EXTRACT LEATHER TRUNK JENGKOL( Archidendron pauciflorum ) AND EXTRACT LEATHER TRUNK GUAVA( Psidium guajava ) - Teguh Irsyadi; Isnaniah '; Irwandy Syofyan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACT This study will be conducted in June 2014 which was held at the Laboratory of Materials Capture Device Utilization of Water Resources of the Faculty of Fisheries and Marine Sciences, University of Riau. The method uses a completely randomized design (RAL) with the untreated control with 10 replications. Yarn PA without treatment breaking strength 11.95 kgf, elongation of 15.35 mm, greeting bark extract (Syzygium polyanthum) 14.95 kgf breaking strength, elongation 18.75 mm, tannins 82,7%, jengkol (Archidendron pauciflorum) strength dropping 14.4 kgf, elongation of 17.5 mm, tannins 70-75 % and guava (Psidium guajava) 12.5 kg breaking strength, elongation 15.5 mm, taninns12 - 30 %. The results of ANOVA test was highly significant sig < 0.01 (11.95 kgf < 14.95 kgf ) of the breaking strength thread untreated very significant effect sig <0.01 (15.35 Mm < 18.75 Mm) to elongation were not given treatment.Keywords : bark extract , End Strength , elongation , Tannins